A Tailored E-Commerce System for Small Automotive Retail Business: The Case of YH Speed - Ooi, Xin Ru; Omar, Nurul Aswa (Applied Information Technology And Computer Science, 2025)
E-commerce refers to the buying and selling of goods or services over the Internet, covering various online transactions including retail, digital services, and online marketplaces. Pusat Tayar & Bateri YH Speed is a small automotive shop in Jitra, Kedah. Currently, it faces issues with manual order handling and outdated tracking of product availability, which often leads to overselling and delays. Its reliance on social media for promotions also limits reach and requires frequent manual updates. To address these issues, an e-commerce system is designed using the Waterfall development model, ensuring a structured approach from requirements gathering to design, implementation, and testing. The system will be developed using PHP for the backend, MySQL for the database, and HTML, CSS, and JavaScript for the frontend. The system is designed to streamline operations, improve customer experience, and increase visibility, helping the business scale and compete effectively. The platform will automate tasks like updating product availability, tracking order status, boosting sales and efficiency while expanding the business’s reach for long-term success.